2017
DOI: 10.1249/mss.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toe-In and Wider Step Width in Stair Ascent with Different Knee Alignments

Abstract: The TIW gait modification seems to be successful in reducing knee joint loading in all three planes during stair ascent, regardless of knee alignment. The success of TIW in varus knee alignments may have important implications for people with medial knee osteoarthritis, or those susceptible to knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies investigating gait modifications in KOA have focused on reporting changes in KAM under standardized laboratory conditions [2][3][4][5][6]24,25] and most trained the gait modifications within a single session (and single-task conditions) only. These studies provide evidence of fast-learning but not of slow-learning, required for longerterm retention of the learnt gait pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating gait modifications in KOA have focused on reporting changes in KAM under standardized laboratory conditions [2][3][4][5][6]24,25] and most trained the gait modifications within a single session (and single-task conditions) only. These studies provide evidence of fast-learning but not of slow-learning, required for longerterm retention of the learnt gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…People with medial knee osteoarthritis (KOA) often have an increased knee adduction moment (KAM), which is associated with faster progression of the disease [1]. Modifying the foot progression angle (FPA) during gait can reduce the KAM [2][3][4][5][6][7][8][9]. Real-time biofeedback can be used to train gait modifications [3][4][5][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking toe-in gait reduces the first peak KAM through lateralising the centre of pressure in early stance and moving the knees to a more medial position [36,37] and toe-out gait reduces the second peak KAM through lateralising the centre of pressure in late stance [35,36]. Reduction of both peaks simultaneously has also been achieved in healthy individuals during stair ascent using a combination of toe-in gait and wider steps [32]; however this has not been replicated in people with medial KOA. Although several studies have shown that gait modifications can indeed reduce the KAM (first or second peak) in the short term (i.e.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In recent years there has been a focus on the use of gait modifications to reduce the KAM. Gait modifications that can reduce the KAM include walking more slowly [28], walking with increased trunk lean [29,30], increased medial thrust of the knee [30,31], increased step width [32][33][34] or modified foot progression angle [35][36][37][38]. Changes in foot progression angle (FPA), walking with toe-in or toe-out gait, are most commonly investigated.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Stair walking is a common motion in everyday life and requires more physical load and range of motion in the lower limb joints than walking on flat ground, resulting in higher energy consumption than ordinary walking. Stair descent has also been reported to have a higher fall risk than stair ascent [1][2] [3].…”
Section: Introductionmentioning
confidence: 99%